Monetary policy, government control and capital investment: Evidence from China - Jing Zhao; Chen Xiao; Ying Hao (China Journal of Accounting Research, 2018)
This study examines how the relationships between local governments and local enterprises moderate the effect of targeted monetary policies through different action-propagating mechanisms. First, we investigate the impact of monetary policies on enterprise investment in areas with different institutional environments. Second, we investigate the impact of monetary policies on state-owned enterprises (SOEs) with different property rights structures. Third, we examine how political connections can influence the action-propagating mechanism of monetary policies. We conclude that in China monetary policies have different effects on SOEs and on private enterprises with or without political connections. Specifically, local government interventions can significantly weaken and distort the effects of monetary policies, such that the intended reduction in investment is noticeably alleviated for SOEs and private enterprises with close links to local governments.
Keywords: E52; G31; M40; 650; Monetary policy; Government intervention; Nature of property rights; Political connection; Capital investment